Hubungan Penggunaan Kontrasepsi Suntik 3 Bulan dengan Kenaikan Berat Badan di Wilayah Kerja Puskesmas Mokoau Kendari Permai Tahun 2016 - Unti, Wa Ode Siti Marwati; Novitasari, Ari (Jurnal Gizi Ilmiah, 2016)
The use of injectable contraceptives, both monthly and quarterly injections, has a major side effect, namely changes in body weight. Factors that influence changes in body weight of injectable contraceptive acceptors are the presence of a strong progesterone hormone that stimulates the appetite hormone in the hypothalamus. The side effect of 3-month injectable contraceptives with the highest frequency is weight gain, the aim is to determine the relationship of 3-month injectable contraceptives with weight gain in the work area of ​​Mokoau Kendari Permai Health Center in 2016. This study used an analytic survey method, with a cross sectional study design approach. The population in this study were acceptors of 3-month injectable contraceptives as many as 105 respondents and the sampling method was simple random sampling technique in the work area of ​​Mokoau Kendari Permai Health Center in 2016. The results of statistical tests using Chi-Square obtained value = 0.000 < = 0.05 then Ho is rejected and Ha is accepted which means there is a relationship between the use of 3-month injectable contraception with weight gain in the work area of ​​Mokoau Kendari Permai Health Center in 2016. Based on the phi coefficient test, a value of 0.479 was obtained, indicating a moderate relationship between the use of 3-month injectable contraceptives and weight gain in the work area of ​​Mokoau Kendari Permai Health Center in 2016. This research can be used as consideration for further research. Through a larger number of respondents and a number of variables, such as age, food intake, lifestyle, activity, etc., as well as midwives and other health workers, they can provide counseling about the side effects of 3-month injectable contraception, there is no concern for acceptors of 3-month injectable contraception.